Optimization the Light-Heat-Biomass Synergistic Hydrogen Production System in High-Altitude - Yang, Xiaoqing; Bai, Shuang (International Journal of Electric Power and Energy Studies, 2026)
In high-altitude areas, resources are abundant and energy consumption is decentralized, and the energy system has not achieved interconnection. Hydrogen energy, as a clean energy source, can fully utilize the resources in high-altitude areas and achieve large-scale utilization of energy and chemicals, cross-time and regional transportation, and integration of various energy sources. Based on this, this paper constructs a multi-energy complementary system including electricity, heat, oxygen, and hydrogen, focusing on multi-path collaborative improvement of hydrogen and oxygen production, full utilization of photothermal resources, and enhancing system economic efficiency. It proposes an innovative operation framework for a photothermal-biomass combined hydrogen production plant. By integrating CO2 electrolysis oxygen circulation technology and photovoltaic green hydrogen auxiliary mechanism, a photothermal-biomass collaborative hydrogen production system is constructed. Firstly, a system mathematical model is built and chemical simulation analysis is conducted to verify the feasibility of the hydrogen production route. Secondly, the energy/energy efficiency of the hydrogen production system is analyzed from the perspectives of hydrogen/oxygen production rate and energy/energy efficiency. Finally, economic analysis is conducted to calculate the levelized hydrogen production cost to verify economic feasibility.